Henry IV, part I - Callow, Simon 1949- (Faber and Faber, 2002)
The Actors on Shakespeare series draws on the contemporary relevance and enjoyment to be found in Shakespeare. Each book contains a personal response to a particular character, in this case the writer and actor Simon Callow on Falstaff
Keywords: Shakespeare, William / 1564-1616 / King Henry IV. / Part 1; Shakespeare, William / 1564-1616 / Characters / Falstaff; Henry / IV / King of England / 1367-1413 / In literature; Shakespeare, William / 1564-1616 / Henry IV, Part 1; Acting